Infrared imaging spectroscopy with micron resolution of Sutter's Mill meteorite grains. (13th October 2014) - Yesiltas, Mehmet; Kebukawa, Yoko; Peale, Robert E.; Mattson, Eric; Hirschmugl, Carol J.; Jenniskens, Peter
Abstract Synchrotron‐based Fourier transform infrared spectroscopy and Raman spectroscopy are applied with submicrometer spatial resolution to multiple grains of Sutter's Mill meteorite, a regolith breccia with CM1 and CM2 lithologies. The Raman and infrared active functional groups reveal the nature and distribution of organic and mineral components and confirm that SM12 reached higher metamorphism temperatures than SM2. The spatial distributions of carbonates and organic matter are negatively correlated. The spatial distributions of aliphatic organic matter and OH relative to the distributions of silicates in SM2 differ from those in SM12, supporting a hypothesis that the parent body of Sutter's Mill is a combination of multiple bodies with different origins. The high aliphatic CH2/CH3 ratios determined from band intensities for SM2 and SM12 grains are similar to those of IDPs and less altered carbonaceous chondrites, and they are significantly higher than those in other CM chondrites and diffuse ISM objects.